The JOBS Act : Crowdfunding Guide to Small Businesses and Startups. - Cunningham, William Michael (Apress, 2016)
The second edition of this book shows how full implementation of the Jumpstart Our Business Startups (JOBS) Act by the SEC in 2016 enables entrepreneurs and SME executives to leverage crowdfunding platforms to raise significant amounts of capital for their startups and small-to-medium--sized businesses. The unprecedented fundraising opportunities contained in the hundreds of pages of new SEC rules have generated tremendous excitement in the startup, small business, angel investing, and venture capital worlds--tempered by uncertainty about the correct interpretation of the rules and the compliance risks implicit in them. In The JOBS Act: Crowdfunding Guide for Small Businesses and Startups, 2nd Edition, crowdfunding pioneer William Michael Cunningham trawls the hundreds of pages of new rules for the essential takeaways and practical tips on successfully tapping the new crowdfunding sources that the JOBS Act opens up to small businesses and startups, while complying with new SEC regulations in the least burdensome way. The 2nd edition of The JOBS Act delivers the following new material: Updates and augments the 1st edition with description, analysis, and discussion of post-2012 SEC rules and forms implementing the JOBS Act Focuses on the final SEC rules that implement Title III ("Regulation Crowdfunding") and Title IV ("Regulation A+") to make the JOBS Act a practical fundraising vehicle for small business and startups Presents case studies of successful JOBS Act-compliant crowdfunding campaigns Tips readers to the opportunities, loopholes, and hazards in the hundreds of pages of new SEC rules that crowdfunders need know to maximize their fundraising success and avoid inadvertent non-compliance Deploys new graphical analysis tools and financial models summarizing and comparing characteristics of various equity-based and donation-based crowdfunding campaigns Reviews and describes significant Title III offerings and highlights relevant Title IV offerings Lists all SEC/FINRA-approved equity crowdfunding platforms ("funding portals") Describes Title VII and provides crowdfunding-pertinent information on the new Offices of Women and Minority Inclusion at twenty-nine federal agencies